Contribution of Eye-Foot Coordination and Agility to Dribbling Skills of Football Players - Ramadhani, Riki; Perdana, Fitryan Dedi; Sani, Asrul (Yayasan Sekora, 2018)
The problem in this study is the low dribbling or dribbling skills performed by football players at SD Negeri 11 Pulau Mungkur, Kuantan Singingi Regency. This study aims to determine the contribution of eye-foot coordination and agility to the dribbling skills of soccer players at SD Negeri 11 Mungkur Island, Kuantan Singingi Regency. This type of research is correlational. The population in this study were all students of SD Negeri 11 Pulau Mungkur, Kuantan Singingi Regency who actively participated in extracurricular activities in the soccer sport, totaling 21 people. The sampling technique used total sampling. Data were collected using measurements of the three variables. the eye-foot coordination variable used the kick test against the target wall, and to measure agility using the 4X10 meter roundtrip test. Meanwhile, the skill of dribbling the ball uses a dodging test. Data were analyzed with product moment correlation and continued with multiple correlation. Based on the results of data analysis, it shows that the first hypothesis is that there is a contribution of eye-foot coordination to ball dribbling skills of 20.43%. The second hypothesis is that there is a contribution of agility to ball dribbling skills by 23.91%. While the third hypothesis is that there is a joint contribution of eye-foot coordination and agility to soccer dribbling skills at SD Negeri 11 Pulau Mungkur, Kuantan Singingi Regency of 35.28%.